The developmental abilities of Thai Children with intellectual disability in storytelling - Sorabud - Rungrojsuwan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Intellectual disabilities, to some extent, play a role in the delay of language development. Research about children with intellectual disability (henceforth, CID) in Thailand has focused on either specific learning skills or basic linguistic knowledge, ignoring overall language development. This study is an attempt to examine the developmental pathway of linguistic features acquired by 29 Thai CID from 9 to 15 years of age. The storytelling technique was employed for data collection using a modified version of the picture book ‘Frog, where are you?’. The children were asked to retell a story, and three aspects of narrative-related features—continuity of events (the use of conjunctions), elaboration of details (NP and VP internal structures), and imagination of narrators (background information and story evaluation)—were used for qualitative data analysis. Results show that, 9- and 13-year-old children’s language performances were quite similar. That is, the variation and complexity of language forms were sporadic. In some features, children in the lower age group showed better performance than those in the older age group. However, it is noticeable that at the age of 15, they could produce more varied forms with a higher degree of complexity. Although CID start to acquire language later than typically-developing children, at about 15 years old they can effectively communicate with complex language structures like typical children. Findings from this study can be used as a guideline for CID- directed language learning and teaching.